Prioritising Conservation Area in Species Management Strategy for The Edible Bornean Giant River Frog Limnonectes leporinus Anderson 1923 - Ramlah, Zainudin; Elvy Quatrin, Deka; Julius, Georgy (Penerbit Universiti Sains Malaysia, 2024)
Abstract: Limnonectes leporinus, the endemic giant river frog, is a riparian (stream dwelling) species that lives along streams with moderate to steep gradients. The most serious threats to the species are deforestation caused by severe clear cutting, which fragments its distribution, and overhunting for local consumption. Excessive landscape modification alters habitat, making it critical for an organism to maintain heterozygozity for the population to be fit to adapt to a changing environment. The goal of this research was to project suitable habitats and predict the potential for habitat connectivity to allow gene flow across the Sarawak landscape. The presence data file and environmental layers were converted into ASCII format using ArcGIS and then used in MaxEnt modelling to generate the map of suitable habitats. To perform the connectivity model, the potential habitat model and genetic attributes of haplotype data were computerised in Circuitscape software. The findings revealed that suitable habitats corresponded to species distribution in lowland areas with sustainable stream networks as breeding sites, while higher elevations were identified as unsuitable habitats. Gene flow data, on the other hand, revealed that connectivity circuits are mostly found in unprotected forest, which includes development areas and private lands. As a result, prioritising conservation areas should include local governments and landowners in proper landscape management as well as species management strategies. This indirectly sustains and protects Borneo’s forests, flora and fauna.